Influence of different ambient luminances on the perception of gray values - Camila Silvério Carvalho VIEIRA; Lorena Mendes ALMEIDA; Francielle Silvestre VERNER; Gabriella Lopes de REZENDE BARBOSA (Revista de Odontologia da UNESP)
Abstract Introduction In clinical practice, dental offices present varying ambient light conditions that may influence the assessment of radiographic exams. Objective Evaluate the influence of ambient light conditions on the contrast sensitivity function in the perception of different densities on dental radiographs. Material and method 55 conventional radiographs of aluminum step-wedges were evaluated by four previously trained and calibrated observers (two undergraduate students and two graduate students) in two environments with different luminance: 50 lux and 500 lux. The radiographs were obtained by positioning two aluminum step-wedges (one fragmented and one intact) with 11 different thicknesses in a periapical film. The fragmented steps were randomly arranged on the upper side of a periapical film while the intact step-wedge was positioned on the bottom part. Over the radiographic series, this arrangement was set respecting a previously standardized organization in five combinations, always maintaining a constant central step. During image analysis, the observers indicated the correspondence of the central fragmented step on the intact step-wedge that served as a reference. After 30 days, 25% of the sample was reevaluated. The statistical analysis was performed using weighted Kappa and Wilcoxon tests. Result The results did not demonstrate statistically significant differences between the data obtained in the same environment with the two different light conditions (p=0.174). However, in both conditions, most evaluations indicated a perception of higher radiopacity in the central step. Conclusion Different ambient light conditions do not interfere with the contrast sensitivity function in the perception of gray values in conventional radiographs.